DAMPAK PANDEMI COVID-19 PADA SEKTOR KULINER DI BALI - Wayan Eny Mariani; I Gusti Ayu Anom; Bagus Kusuma Wijaya (Fakultas Ekonomi Universitas Warmadewa, 2022)
The whole world is currently facing the COVID-19 pandemic or also known as the Corona virus. Positive cases infected with the corona virus have now spread in 223 countries. Indonesia is the fourth most populous country in the world and is expected to be significantly affected over a longer period of time. The impact of this pandemic is not only on the world of health, but has also penetrated almost all aspects of social life where people and companies have been urged to carry out restrictions on their activities. This appeal resulted in many companies being unable to operate as usual. One of the business fields affected by the pandemic is a business engaged in the culinary field. This study aims to see the impact of the Covid-19 pandemic on MSMEs, especially those engaged in the culinary field in Bali Province. The results of this study found that the COVID-19 pandemic resulted in a decrease in the growth of gross regional domestic product in Bali.